MOTIVATIONAL MESSAGES OF THE SELECTED SONG MICHAEL JACKSON IN ALBUM “DANGEROUS” - Amalia, Meriani; bakri, Fitriyani (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is a study on “Motivational Messages of The Selected Song Michael Jackson In Album Dangerous” This research has 2 objectives, namely to find out the motivation message of the selected song Michael Jackson in album “Dangerous” and how do the lyrics of the selected song Michael Jackson in album “Dangerous” motivate listeners. This research uses a semiotics qualitative method by Ferdinand de Saussure to find signifiers and signified. The signifier and the signified of lyric song illustrate the connected nature of language and thought that have impact to intrinsic and extrinsic motivation. The data that will be used in this research is the lyrics of the song Michael Jackson. Data collection may include observation and analysis of records, reports. As a result, qualitative research is seen as an appropriate method to complete this research. Finding motivational messages was the method used to obtain data for this research. The researcher lines that showed part of the messages contained in the lyrics of the song. After gathering all the information then discuss and develop its conclusions based on the findings of data analysis.